Assessment of marital dissatisfaction and its association with sexual dysfunction and psychiatric morbidities among primary health attenders in Malaysia - S, Ahmad Faizal; Sidi, Hatta; Wahab, Suzaily; Drph, Leny Ss; Mat Zin, Nora; Baharuddin, Najwa (International Islamic University Malaysia, 2017)
Introduction: Marital satisfaction is vital to the wellbeing and functioning of the individual and family. Marital dissatisfaction can lead to detrimental effects on mental, physical and family health. The study aimed to determine the proportion of marital dissatisfaction in outpatient setting and its association with sexual functioning and psychiatric morbidity in Kuala Lumpur, Malaysia. Materials & Methods: A crosssectional study was conducted in selected primary care using purposive sampling. Data collection was done using socio-demographic questionnaire and several validated Malay version of self-administered questionnaires. Marital satisfaction was measured by the Malay version of Golombok–Rust Inventory of Marital State (Mal-GRIMS). Results: The prevalence of marriage dissatisfaction in sample population was about 37.3% with almost equal prevalence in both, 36.5% (male) and 37.8% (female). Using a regression analysis, the significant factors that affect marital dissatisfaction were respondent’s age group between 31- 40 years old (Adjusted Odds Ratio, AOR. =11.4, 95% Confidence Interval, CI. =1.2-110.9), spouse’s salary ofRM1000-RM2000 (lower income category) (AOR=7.3, 95% CI= 1.9-28.1), anxiety case (AOR= 4.8, 95% CI=1.1-21.5), depression case (AOR= 4.8, 95% CI=1.0-22.8), female sexual dysfunction in term of arousal function (AOR= 0.01, 95% CI=0.0-0.7), satisfaction dysfunction (AOR= 9.4, 95% CI= 1.5-58) and pain function(AOR=43.7, 95% CI=1.28 - 1489.2). Conclusion: Marital dissatisfaction can be influenced by financial factor,sexual dysfunction and presence of psychiatric morbidity. Hence, in management of marital discord, thorough screening of these factors should be prioritized in clinical setting.